Applying Total Station Technology to Enhance Student Competencies in a Vocational Education Institution - Taufiq Natsir; Ridwan Ridwan; Ishak Ishak; Ahmad Wahidiyat Haedar; Ramli Rasyid (PT. Global Research Collaboration, 2025)
This community engagement program aims to enhance the technical competencies of students in a vocational education institution through the application of Total Station technology for contour measurement. The initiative was designed to bridge the gap between classroom theory and modern field surveying practices by integrating structured training, intensive mentoring, and digital mapping tools. A total of 30 geomatics students participated in the program, engaging in instrument familiarization, field measurement exercises, and data processing using CAD-based mapping software. The training adopted an experiential learning model with a learning-by-doing approach, supported by digital modules and instructional video tutorials. Evaluation results show substantial improvements in student competencies: 85% of participants were able to operate the Total Station independently, 70% processed survey data digitally, and 80% produced contour maps of acceptable quality. The program also generated a digital learning module as a sustainable output. These findings demonstrate that integrating Total Station technology into vocational education effectively improves students’ understanding of topography, spatial data analysis skills, and industry-oriented work readiness.